The Higher Education Dimension in East Asian Regionalism: A Two-tier Analysis of International Co-authorship Patterns in the ASEAN Plus Three - Oliver Gill (JAS (Journal of ASEAN Studies), 2018)
The AUN and ASEAN+3 UNet have both sought to promote the development of a distinct higher education research community within Southeast Asia and East Asia, respectively. The purpose of this paper is two-fold. Firstly, it aims to assess the success of these organisations in delivering against this aim, reviewed against inter-regional comparators. Secondly, the paper undertakes an assessment of which countries (if any) might be predominant in driving this agenda forward, at the intra-regional level. In both levels of the investigation, a statistical analysis of changes in international co-authorship patterns across time is utilised as the means of assessing the question at hand. In accordance with the paper’s core hypotheses, the findings indicate broad fulfilment of the AUN and ASEAN+3 UNet’s objectives, although it seems that efforts directed at building an East Asian research community have been comparatively more successful than those directed specifically at Southeast Asia. It is also found that, in a relative sense, South Korea is acting as a principal locus for higher educational regionalisation. The paper concludes by considering the implications of the analysis for East Asian higher education regionalism, with the contention being that the establishment of the aforementioned research communities provides a robust basis for the development of more formal integrative measures.